First aid manual for Filipinos Pangunahing lunas para sa Pilipino. - Philippine General Hospital. Emergency Room Complex; Philippine Society of Emergency Care Physicians (Manila Emergency Room Complex, Philippine General Hospital, 1993)
Illustrated guidelines not only for the medical professionals and its allied health workers, but more especially for the general population.
A manual that serves as a guide on first aid for the use of the general population of the country.
Jointly published with Philippine Society of Emergency Care Physicians.
Title from cover.
Keywords: First aid in illness and injury -- Philippines -- Handbooks, manuals, etc